THE COMMUNICATIVE COMPETENCE MODEL IN FOREIGN LANGUAGE EDUCATION - Erkinova Farzona (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
The communicative competence model has become a cornerstone of modern foreign language education. Unlike traditional grammar-based approaches, this model emphasizes the learner’s ability to use language effectively and appropriately in real-life communicative contexts. This article examines the theoretical origins of communicative competence, its structural components, its evolution through different models, and its pedagogical implications. Drawing upon the works of Hymes (1972), Canale and Swain (1980), Bachman (1990), and Celce-Murcia et al. (1995), the study highlights the significance of communicative competence in shaping contemporary communicative language teaching (CLT). The article also discusses the model’s relevance in the digital era and multilingual educational contexts.